2013
DOI: 10.1590/s1519-99402013000100009
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da adição de probiótico em dietas de leitões desmamados sobre as características do sistema digestório e de desempenho

Abstract: Os objetivos foram avaliar os efeitos da adição de diferentes concentrações de probiótico (0; 200 e 300mg/kg de ração) em rações de leitões recém desmamados e em diferentes idades de abate, sobre as características do sistema digestório e desempenho zootécnico. Foram utilizados 35 leitões desmamados, distribuídos em delineamento em blocos casualizados em esquema fatorial 3x2+1 (três concentrações de probiótico x duas idades de abate + grupo abatido ao desmame). Foram abatidos cinco leitões no dia da desmama e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
1
1
3
Order By: Relevance
“…The supply of probiotics to suckling piglets did not affect their average daily feed intake or the incidence of diarrhea; however, it improved average daily weight gain, independently of genetic line. These results are different from those obtained by RoBlES-HUAYNATE et al (2013), who observed better feed intake in suckling piglets orally supplied with a probiotic product, but no differences in weight gain or in the incidence of diarrhea. The higher average daily weight gain observed with the supply of probiotics in the present experiment may be related to better intestinal capacity of nutrient absorption, as shown by the higher duodenal and jejunal villus height measured in the probiotic-supplied piglets.…”
Section: Effect Of Probiotic Supplycontrasting
confidence: 99%
“…The supply of probiotics to suckling piglets did not affect their average daily feed intake or the incidence of diarrhea; however, it improved average daily weight gain, independently of genetic line. These results are different from those obtained by RoBlES-HUAYNATE et al (2013), who observed better feed intake in suckling piglets orally supplied with a probiotic product, but no differences in weight gain or in the incidence of diarrhea. The higher average daily weight gain observed with the supply of probiotics in the present experiment may be related to better intestinal capacity of nutrient absorption, as shown by the higher duodenal and jejunal villus height measured in the probiotic-supplied piglets.…”
Section: Effect Of Probiotic Supplycontrasting
confidence: 99%
“…Observou-se maior resposta (P<0,05) para leucócitos, nos tratamentos que receberam prebióticos e probióticos, seguidos dos tratamentos contendo antibiótico e controle, aos 54 dias de idade dos animais. As principais células de defesa do organismo são representadas pelos leucócitos, incluindo linfócitos, monócitos, neutrófilos e eosinófilos, e são fortemente influenciadas pela nutrição, estresse ou desordens clínicas (15) . Robles-Huaynate et al (15) relataram aumento na contagem de leucócitos em função da desmama dos leitões e sua diminuição em função da adição de probióticos nas rações.…”
Section: Resultsunclassified
“…As principais células de defesa do organismo são representadas pelos leucócitos, incluindo linfócitos, monócitos, neutrófilos e eosinófilos, e são fortemente influenciadas pela nutrição, estresse ou desordens clínicas (15) . Robles-Huaynate et al (15) relataram aumento na contagem de leucócitos em função da desmama dos leitões e sua diminuição em função da adição de probióticos nas rações. O efeito imunoestimulante em animais pode estar relacionado à capacidade de os microrganismos com características probióticas interagirem com as placas de Peyer e as células epiteliais intestinais, estimulando as células B produtoras de IgA e a migração de células T do intestino (36) .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…In the case of probiotics, benefits in growth, weight gain improvement, feed conversion (Musa, Wu, Zhu, Seri, & Zhu, ), and carcass output and quality (Jukna, Jukna, & Simkus, ) have been reported. The physiological action of probiotics depends mainly on the establishment of the beneficial intestinal flora (O′Toole & Cooney, ), which decreases the competitive ability of pathogenic bacteria (Robles‐Huaynate et al., ). Probiotic bacteria can be viable microorganisms in wet, frozen and lyophilized preparations or as fermented products (Gaggìa, Mattarelli, & Biavati, ; Utiyama, Oetting, Giani, Ruiz, & Miada, ).…”
Section: Introductionmentioning
confidence: 99%